LEXICAL UNITS: APPROACHES AS WORDS, TERMS AND NEOLOGISMS - Hurshid Sarimsokov; Madina Ravshanova; Malohat Badalbaeva; Nargiza Sultanova (The Bioscan, 2024)
In this article, the system-structural direction of linguistic is important in understanding the essence of lexical units, words, terms and neologisms, organizing and systematizing newly improving lexical units. Scientific research works, monographs, training manuals and textbooks devoted to scientific theories and their application, expression and characterization are analyzed in the field of linguistics.